Haematological and serum biochemical variables in rats treated with ethanol extract of the root of moringa oleifera (2014)
The haematology and serum biochemical effects of oral administration of the ethanolic extract of the root of Moringa oleifera at 50, 100 and 150 mg/kg were investigated in 30 mated female Wistar rats. The rats were assigned into five groups of six rats each. Group A was given 50mg/kg of the extract; group B, 100mg/kg; group C, 150 mg/kg; group D, 0.2ml of corn oil; and group E, 0.2ml of distilled water. Groups D and E, corn oil and distilled water treatment groups respectively, served as the controls while groups A, B and C were the treatment groups. There was no significant difference (P>0.05) between the two control groups and the treatment groups for the RBC, WBC, PCV, MCV, MCH and MCHC and Hb. However, the mean lymphocyte values for groups B and C were significantly different (P<0.05) from those of group A as well the two control groups. The total protein, albumin, globulin and A/G ratio showed no significant difference (P>0.05) between the two control groups and the treatment groups. There were no significant differences (P>0.05) in the values of AST, ALP, creatinine, urea, GGT, glucose, cholesterol and ALT between the treatment groups and the control groups. It can therefore be concluded that oral administration of ethanolic extract of the root of M. oleifera is harmless to the rats since no adverse effects were detected in haematological and serum biochemical investigations